The influence of retirement goals and risk attitudes on Malaysian women's retirement planning - Mohd Yaziz bin Mohd Isa; Mellisa Daukin (Cogent Economics & Finance, 2023)
The lack of retirement savings for the future lives of many individuals, and pre-retirees in particular, is an example of one of the most critical problems facing many emerging countries. Unfortunately, a lack of preparedness can have severe effects on Malaysian cultures, especially for women who are nearing retirement. The issues persist and, most likely, are becoming worse despite all the awareness campaigns that have been running for a while. In order to express fresh thoughts and suggest an extra approach or workable solution to supplement past research and conclusions, this study will analyse this dilemma from a women's perspective of retirement planning. This study applies a quantitative approach, where primary data was acquired through online surveys of 443 workers in various locations in Malaysia. Validation of the measurement model in this study uses the structural equation model (SEM), which interprets that if the model fits, the strength of path estimates, validity, and reliability of the construct are estimated. The results of this study show that retirement goals affect an individual's retirement planning, but risk perception does not affect an individual's perspective on planning for a future retirement. This study also emphasises the significance of financial literacy in retirement planning, specifically how it will boost the confidence of these female workers as they approach retirement. These findings also have useful ramifications for financial planners and advisors, enabling them to better comprehend the variables influencing retirement saving behaviour.
Keywords: 330; attitude to risk; gender; retirement goal; retirement planning; women